Conceptualizing Leader–Member Exchange as a Second-Order Construct - Manata, Brian; Grubb, Siri (Frontiers in Psychology, 2022)
To date, scholars have focused a considerable amount of effort on developing valid measures of leader-member exchange (LMX). Although useful, it is unclear whether this proliferation in measurement is warranted. Specifically, although perhaps meaningful conceptual distinctions are made when developing new LMX measures, it is unclear whether these measures differ sufficiently from previously established measures. This manuscript explores this possibility. We begin by providing a brief review of the current state of LMX measurement, and then proceed by describing three different studies through which this research question is explored. Results suggest that virtually all measures of LMX included in this investigation are indicators of the same underlying second-order factor, i.e., they are all measuring the same construct.